Effect of glutamine ingestion on the progression of induced periodontitis: experimental study in rats - Aurélio Rosa da SILVA JUNIOR; Alex SEMENOFF SEGUNDO; Tereza Aparecida Delle Vedove SEMENOFF; Natalino Francisco da SILVA; Cervantes CAPOROSSI
Abstract Introduction With glutamine supplementation there is better performance in the body's defense system. Objective The aim of this study was to analyze the effect of glutamine supplementation on ligand-induced periodontal disease in rats. Material and method 48 selected male Wistar rats were divided into 4 groups (N = 12): control group (CG) including healthy animals receiving daily saline solution via gavage; glutamine group (GG) including healthy animals receiving oral glutamine supplementation by gavage at a dose of 1.5 g / kg / day; periodontitis group (PG) including animals with induced periodontal disease on both upper sides receiving daily saline solution via gavage; experimental group (EG) including animals with induced periodontal disease on both upper sides receiving daily glutamine via gavage at a dose of 1.5 g / kg / day. On the 30th day, all animals were euthanized by excess anesthetic. Result In the various analyses, the EG (116.63 ± 22.50 mm2) compared to the CG (82.32 ± 7.48 mm2) obtained a p<0.05. The PG (143.15 ± 35.24 mm2) compared to the EG group (116.63 ± 22.50 mm2 ) presented a p<0.05. The PG (143.15 ± 35.24 mm2) compared to the CG (82.32 ± 7.48 mm2) presented a p<0.05. The GG (118.09 ± 10.4 mm2) compared to the CG (82.32 ± 7.48 mm2) presented a p>0.05. Conclusion Glutamine supplementation associated with induced periodontal disease demonstrated a smaller amount of bone loss compared to the periodontitis group.